Pola makan dan aktivitas fisik sebagai faktor risiko diabetes melitus tipe 2 pada karyawan generasi Z - Oktora, Rindha; Junita, Dera Elva; Wati, Desti Ambar; Nurhayati, Aftulesi (ARGIPA (Arsip Gizi dan Pangan), 2025)
Diabetes mellitus (DM) is a metabolic disorder characterized by elevated blood glucose levels and has become one of the emerging health concerns among Generation Z (Gen Z). Diet and physical activity are major risk factors for the development of diabetes mellitus. Unhealthy eating habits and sedentary lifestyles can lead to increase blood glucose levels and a higher risk of insulin resistance. This study aimed to determine the correlation between dietary patterns and physical activity levels of Gen Z employees with random blood glucose status and the risk of type 2 diabetes mellitus. This research employed a quantitative analytical design with a cross-sectional approach. The study population consisted of 477 Gen Z employees, and a sample of 204 participants was selected using the purposive sampling technique. Research instruments included a dietary questionnaire using the Semi-Quantitative Food Frequency Questionnaire (SQ-FFQ), a physical activity questionnaire using the International Physical Activity Questionnaire (IPAQ), and blood glucose examination using the Easy Touch GCU device. Data were analyzed using the Gamma test. The results from 204 subjects showed that 191 subjects (93.6%) had unbalanced diets, 161 subjects (78.9%) had low physical activity levels, and 116 subjects (56.9%) had normal random blood glucose levels. There was a significant correlation between the dietary patterns of Gen Z employees and random blood glucose status with the risk of type 2 diabetes mellitus (p=0.000), as well as a significant correlation between physical activity levels and random blood glucose status with the risk of type 2 diabetes mellitus (p=0.023). It is expected that these findings can be used as a reference for dietary service guidelines for individuals at risk of or living with diabetes mellitus.